Geopolitics as the elder sister of geoeconomics and the transformation of the world system in the 21st century - Cvetićanin, Neven; Maksimović, Marijana (Sociološki pregled, 2023)
The subject of the undertaken research is the analysis of geopolitical and geoeconomic changes in the multipolar world of the 21st century, which lead to the transformation of the world system. There is an ongoing evolution of the geostrategic position of the United States of America (USA), the rise of China, as well as the division of the world that occurred with the offensive activities of Russia and the expansion of other countries such as India, Brazil, and Saudi Arabia. The goal of the research is to emphasize, in addition to the basic geopolitical component, the importance of the geoeconomic component, as derived, in international relations, which is often less clearly visible in the background of many international conflicts and alliances. The main thesis of the paper is that dominant geostrategic powers such as the USA, China and Russia follow their long-term geopolitical and geoeconomic interests and goals putting them into conflicting or allied relations, which is again responsible for the configuration of power and the relationship between the great powers in the arena of world politics. The paper applies a multidisciplinary combined method that is based on political and economic sciences, and sometimes studies broader geopolitical processes or focuses on a narrower geoeconomic analysis of individual parameters.
Keywords: world system; transformation; multipolarity; geopolitics; geoeconomics